Longterm Effect Of Phenytoin On Lipid Profile Parameters In Epileptic Patients - Beg, M; Afzaal, S; Kamal, A; Amir, A (Indian Journal of Community Health, 1997)
Research Problem: What are the factors responsible for decreased incidence of coronary artery disease in epileptics? Objectives: To evaluate the effect of phenytoin on lipid profile parameters in epileptics and to discuss its implications. Study Design: Prospective study. Setting: Neurology clinic of Medicine Department of a teaching hospital. Participants: Randomly selected epileptic patient attending neurology clinic and admitted to inpatient department of J. N. Medical College Hospital. Sample Size: 56 epileptic patients. Study Variables: Phenytoin therapy, lipid profile parameters. Statistical Analysis: By test of significance. Result: No significant change in serum levels of total cholesterol, LDL - C, VLDL - C, triglycerides and phospholipids was observed with phenytoin therapy during study. However, serum HDL - C showed a significant increase, both at 12 weeks and 24 weeks ( P < 0.001) of therapy. Conclusion: Phenytoin, a commonly used anticonvulsive drug, increases serum HDL - C level significantly, while there is no significant change in other parameters of lipid profile. This rise in HDL - C may provide protection to epileptic patients against atherogenic vascular diseases including coronary artery disease.